2005
DOI: 10.1111/j.1365-2842.2004.01437.x
|View full text |Cite
|
Sign up to set email alerts
|

All‐ceramic fixed partial dentures designed according to the DC‐Zirkon® technique. A 2‐year clinical study

Abstract: The aim of the study was to investigate whether the properties of a pre-sintered, hot isostatic post-compacted (HIP) ZrO2 are adequate for use in three-five-unit fixed partial dentures (FPDs) and to evaluate the clinical results. Twenty three-five-unit FPDs were fabricated for 18 patients on a total of 56 abutments. They were all made on abutments cut with a shoulder preparation and cemented with a zinc phosphate cement. They were clinically followed for 24 months. After 24 months all FPDs were still in use wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
260
2
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(281 citation statements)
references
References 14 publications
9
260
2
10
Order By: Relevance
“…In recent years, CAD/CAM production has clearly expanded the palette of materials for dental prosthe ses by providing access to new ceramic materials with high dependability. 15,[28][29][30][31] The stability values of zirconium oxide ceramics permit, in many areas of indi cation, the use of this material as an alternative to metal frames for perma nent prostheses. 30 The production of long-term temporary prostheses has, as a result of the use of a virtual wax up on the computer, become faster, more convenient and more pre dictable.…”
Section: Significance For the Dentistmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, CAD/CAM production has clearly expanded the palette of materials for dental prosthe ses by providing access to new ceramic materials with high dependability. 15,[28][29][30][31] The stability values of zirconium oxide ceramics permit, in many areas of indi cation, the use of this material as an alternative to metal frames for perma nent prostheses. 30 The production of long-term temporary prostheses has, as a result of the use of a virtual wax up on the computer, become faster, more convenient and more pre dictable.…”
Section: Significance For the Dentistmentioning
confidence: 99%
“…15,[28][29][30][31] The stability values of zirconium oxide ceramics permit, in many areas of indi cation, the use of this material as an alternative to metal frames for perma nent prostheses. 30 The production of long-term temporary prostheses has, as a result of the use of a virtual wax up on the computer, become faster, more convenient and more pre dictable. This method has already been implemented by computer-generated long-term temporary restorations, since it can be modified, by changing the form, to the functional and aesthetic sat isfaction of the patient during a clinical test phase.…”
Section: Significance For the Dentistmentioning
confidence: 99%
See 1 more Smart Citation
“…Zirconia has high flexural strength, fracture toughness and elasticity modulus (Evans, 1990;Filser et al, 2001;Sturzenegger et al, 2001;Lüthy et al, 2005;Fischer and Stawarczyk, 2007) and is highly biocompatible (Piconi and Maccauro, 1990). Clinical studies reported also high survival rate of zirconia frameworks but more failures of veneering ceramic (Vult von Steyern et al, 2005;Raigrodski et al, 2006;Sailer et al 2007;Edelhoff et al 2008;Schmitt et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…For this, dental materials with tooth-like optical properties such as ceramics are preferred. Oxide ceramics, particularly zirconia, are gaining attention because of their good biocompatibility, high strength and excellent load-bearing capacity (Piconi et al, 1999;Sailer et al, 2006;Vult von Steyern et al, 2005) .…”
Section: Introductionmentioning
confidence: 99%